Global research trends in transcranial magnetic stimulation for stroke (1994–2023): promising, yet requiring further practice - Li, Xin-Yu; Hu, Rong; Lou, Tian-Xiao; Liu, Yang; Ding, Ling (Frontiers in Neurology, 2024)
Background Scholars have been committed to investigating stroke rehabilitation strategies over many years. Since its invention, transcranial magnetic stimulation (TMS) has been increasingly employed in contemporary stroke rehabilitation research. Evidence has shown the significant potential of TMS in stroke research and treatment. Objective This article reviews the research conducted on the use of TMS in stroke from 1994 to 2023. This study applied bibliometric analysis to delineate the current research landscape and to anticipate future research hotspots. Method The study utilized the Web of Science Core Collection to retrieve and acquire literature data. Various software tools, including VOSviewer (version 1.6.19), CiteSpace (version 6.3.R1), Scimago Graphica (version 1.0.36), and WPS (version 11572), were used for data analysis and visualization. The review included analyses of countries, institutions, authors, journals, articles, and keywords. Results A total of 3,425 articles were collected. The top three countries in terms of publication output were the United States (953 articles), China (546 articles), and Germany (424 articles). The United States also had the highest citation counts (56,764 citations), followed by Germany (35,211 citations) and the United Kingdom (32,383 citations). The top three institutions based on the number of publications were Harvard University with 138 articles, the University of Auckland with 81 articles, and University College London with 80 articles. The most prolific authors were Abo, Masahiro with 54 articles, Fregni, Felipe with 53 articles, and Pascual-Leone, Alvaro with 50 articles. The top three journals in terms of article count were Neurorehabilitation and Neural Repair with 139 articles, Clinical Neurophysiology with 128 articles, and Frontiers in Neurology with 110 articles. The most frequently occurring keywords were stroke (1,275 occurrences), transcranial magnetic stimulation (1,119 occurrences), and rehabilitation (420 occurrences). Conclusion The application of TMS in stroke research is rapidly gaining momentum, with the USA leading in publications. Prominent institutions, such as Harvard University and University College London, show potential for collaborative research. The key areas of focus include post-stroke cognitive impairment, aphasia, and dysphagia, which are expected to remain significant hotspots in future research. Future research should involve large-scale, randomized, and controlled trials in these fields. Additionally, identifying more effective combined therapies with rTMS should be a priority.